Kelimpahan Populasi Liriomyza spp. (Diptera: Agromyzidae) pada Sentra Tanaman Tomat dan Kentang di Bali - GUSTI AYU INTAN ARI LESTARI; I NYOMAN WIJAYA; DWI WIDANINGSIH (Agrotrop : Journal on Agriculture Science, 2023)
Population Abundance of Liriomyza spp. (Diptera: Agromyzidae) at the Tomato and Potato Center in Bali. The study aims to understand the structure of the community, population, and to determine the relationship between population groups of Liriomyza spp. on tomato and potato plants in Bali. The research was conducted from September 2021 to February 2, 2022, at an altitude of 750-1250 masl, located in Tabanan Regency, Buleleng Regency, Badung Regency and Bangli Regency. The sampling method was purposive and the number of samples taken was 150-250 leaves per location. Identification of Liriomyza spp. carried out in the Laboratory of Integrated Pest Management, Faculty of Agriculture, Udayana University. The results showed that the population of Liriomyza spp. on various tomato and potato crops in the medium and highlands of Bali. The community structure of Liriomyza spp. varied on each plant in the medium and highlands in Bali, with a species diversity index and a low population index and moderate dominance index. The results showed that the population relationship of Liriomyza spp. on tomato and potato plants in Bali from the results of the Paired Sample T Test showed that the population of liriomyza spp. higher in tomato plants than in potato plants.